PS 16-06 A SERINE PROTEASE INHIBITOR INCREASES FREE WATER EXCRETION IN NORMAL RATS. (September 2016) - Kakizoe, Yutaka; Nakagawa, Terumasa; Miyasato, Yoshikazu; Izumi, Yuichiro; Kuwabara, Takashige; Adachi, Masataka; Miyoshi, Taku; Kitamura, Kenichiro; Mukoyama, Masashi
Abstract : Objective: The epithelial sodium channel (ENaC) is activated via the proteolytic cleavage of α and γ subunits by serine proteases (SPs). We reported that cleavage of γENaC by SPs was increased in the kidney of Dahl salt-sensitive rats with high-salt diet and that a synthetic SP inhibitor camostat mesilate (CM) attenuated hypertension and kidney injuries in those rats. In addition, we demonstrated that CM inhibited the cleavage of γENaC in aldosterone-infused rats. These results suggest the important roles of SPs within the kidney in the regulation of sodium homeostasis and blood pressure. However, physiological roles of SPs in the kidney still remain unclear. In this study, we administrated CM to normal rats in order to explore novel physiological roles of SPs in renal tubule. Design and method: Six-week-old male Sprague-Dawley rats were divided into control and CM groups. CM group rats were subcutaneously implanted with sustained-release pellets of CM (14 mg/day). After 24h urine collection was performed, rats were sacrificed at day 7 to obtain blood and kidney samples. Results: CM significantly increased urine volume in about two fold throughout the experimental period independently of sodium and osmolyte excretion, indicating that CM increased osmotic free water excretion. The levels of vasopressin, potassium and calcium in blood as well as osmolality in the inner medulla, that is important for urine concentration, were not changed by CM. CM increased mRNA expression of aquaporins and urea transporter, indicating the compensatory induction of these molecules against water loss. Serine protease-specific zymography demonstrated that the activities of SPs in urine were substantially changed by CM. Conclusions: Our results suggest that SPs are associated with water homeostasis in the kidney. Further studies are necessary to reveal the mechanisms by which SPs regulate the reabsorption of water in renal tubule.